(3eTcdGJ GdUMjMjfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3CMeO Hf YHO GdOGFe Hf fYeg GdebOSi s)
(3ChdgG (B:s
(3bGd GdEeGe LeGd GdOjf CHh GdaQL YHO GdQMef Hf eMeO GdLhRi hai GdMOjK GdMGOi hGdSJjf hbO LGA ai MOjK BNQ WjH GdQLGd eG Nai dhfg s
(3BNQgG (B:s
(3jfJgi HcTa GdeTcd ef eSfO Ce GdOQOGA s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdMOjK h GdeUWdMs